A proposal for an exploratory study on cultural appropriation of T’boli textile and design in commercial fashion - Mata, Maria Kyra M.
Cultural appropriation has been a topic of great debate in recent years as the term enters into the lexicon of many. The increasing presence of indigenous textile and design incorporated into commercial fashion products has aroused uncertainty among members of the majority culture in the Philippines in light of cases of cultural appropriation found in popular culture. Limited research has been done on cultural appropriation in the Philippine local context and more so, on the recontextualization of T’boli textile and design in commercial fashion products. Hence, this paper seeks to propose a research with the general objective of developing a concept of cultural appropriation for T’boli textile and design. To do so, the paper proposes a participatory research approach. The presentation of findings related to the cultural appropriation of T’boli cultural textile and design to the National Commission on Indigenous Peoples is the first step followed by further consultations and involvement of research partners from the community. Researchers of the study will employ indigenous research methods of pakapa-kapa and pagtatanong-tanong to develop a research methodology and instrumentation for ginabayang-talakayan with community stakeholders. In light of restrictions in conducting field research and in consideration of high ethical standards for research surrounding indigenous peoples, this paper is limited to a participatory research approach to allow for further development.